2019
DOI: 10.5154/r.rchscfa.2018.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Actividad proteolítica de frutos silvestres de Bromelia karatas L. de Yucatán, México

Abstract: Introducción: Las bromelias son fuente de proteasas que no se han estudiado totalmente. Objetivos: Evaluar la actividad proteolítica de frutos silvestres de Bromelia karatas L. bajo distintas condiciones de temperatura, pH y NaCl, y estimar la estabilidad térmica de las proteasas. Materiales y métodos: Se comparó el efecto del pH (6, 7, 8, 9, 10 y 12), temperaturas de incubación (30, 40, 50, 60 y 70 °C) y concentraciones de NaCl (5, 10 y 20 %) sobre la actividad proteolítica de los frutos. La estabilidad tér… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We determined the bactericidal activity of the B. karatas fruits' methanolic extract (ME) against E. coli, S. enteritidis, S. flexneri, and E. faecalis (causal agents of human infections) [5,20]; it was shown that these results are consistent with those reported in Bromelia pinguin [6]. We found that the bactericidal activity resisted the sterilization temperature, meaning its potential benefits are still maintained when the fruits are consumed cooked since cooking is necessary to avoid oral injuries caused by their proteolytic activity [11]. In another study, it was determined that the protein extract of the fruits had bactericidal activity, but this was not resistant to heat [14,15], which differs from the heat-resistant bactericidal activity of the methanolic extract found in the present study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We determined the bactericidal activity of the B. karatas fruits' methanolic extract (ME) against E. coli, S. enteritidis, S. flexneri, and E. faecalis (causal agents of human infections) [5,20]; it was shown that these results are consistent with those reported in Bromelia pinguin [6]. We found that the bactericidal activity resisted the sterilization temperature, meaning its potential benefits are still maintained when the fruits are consumed cooked since cooking is necessary to avoid oral injuries caused by their proteolytic activity [11]. In another study, it was determined that the protein extract of the fruits had bactericidal activity, but this was not resistant to heat [14,15], which differs from the heat-resistant bactericidal activity of the methanolic extract found in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…The genus Bromelia includes species that grow wild in Mexico and their fruits are known for their antifungal [7], bactericidal [6,8], and anthelmintic [9] activity. Bromelia karatas fruits contain antioxidants, proteases, and phenolic compounds, such as flavonoids, phenylpropanoids, terpenes, and coumarins [10,11]. Throughout tropical America, B. karatas fruits are consumed as foods and beverages, and their stems can be used as living fences.…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated the proteolytic activity of B. karatas fruits under different conditions of temperature, pH and NaCl, and estimated the thermal stability of their proteases. They found that the bactericidal activity resisted the sterilization temperature, its potential benefits are still maintained when fruits are consumed cooked, cooking is necessary to avoid oral injury caused by its proteolytic activity (Villanueva-Alonzo et al, 2019).…”
Section: Bromelia Karatas Lmentioning
confidence: 99%
“…The obtaining of new sources of plant proteases is increasing due to their low production costs, relative abundance in some plants and attractive biochemical characteristics [25], such as their stability over a wide range of pH and temperature [26]. The fruits of Bromelia pinguin "guamara" and Bromelia karatas "cocuixtle" are presented as an alternative to obtaining plant proteases [4,[26][27][28][29]. However, little information exists on the application of these sources of proteases in different food matrices to obtain protein hydrolysates.…”
Section: Introductionmentioning
confidence: 99%